EDUKASI PENCEGAHAN STUNTING MELALUI PRODUK NUTRACEUTICAL NUGGET SINGKONG DI DUSUN BABAAN SELATAN, DESA NGASEM - Aulan nadiya; Dina Nur Afida; Tsabitah Daffa' Aulia Akmal; Yustisia Sifaiyya; Alifia Putri Febriyanti (UIN Sunan Kalijaga, 2024)
Stunting is one of the serious problems related to child growth, one of the causes of which is the lack of nutritional intake in the form of food provided. The purpose of the activities carried out is preventive action through empowerment focused on three categories that are the main targets, namely mothers of toddlers, pregnant women, and breastfeeding mothers with a demonstration of making nutraceutical products as an effort to reduce the risk of stunting. The method used is CBR (community-based research) which focuses on problems that have occurred and the development of new solutions. The implementation of stunting education was carried out in the form of material presentations by three resource persons, application of cassava-based nutraceutical products, and questions and answers for participants who attended. The results of the activity showed an increase in participants' understanding of stunting and its prevention efforts. This can be seen from the enthusiasm when answering the speaker's questions. The implementation of activities also increases the ability to process surrounding food ingredients into stunting prevention products. The aspects of understanding and processing nutraceutical products are empowerment efforts that have been successfully carried out and are the objectives of the procurement of activities. ================================================ Stunting merupakan salah satu permasalahan serius terkait pertumbuhan anak yang salah satu penyebabnya adalah kurangnya asupan gizi dalam bentuk makanan yang diberikan. Tujuan dari kegiatan yang dilakukan adalah tindakan preventif melalui pemberdayaan yang difokuskan kepada tiga kategori yang menjadi sasaran utama, yakni ibu balita, ibu hamil, dan ibu menyusui dengan demonstrasi pembuatan produk nutraceutical sebagai upaya penurunan resiko stunting. Metode yang digunakan adalah CBR (community-based research) yang berfokus pada permasalahan yang pernah terjadi dan pengembangan solusi terbaru. Pelaksanaan edukasi stunting dilakukan dalam bentuk presentasi materi oleh tiga orang narasumber, penerapan produk nutraceutical berbahan dasar singkong, dan tanya jawab bagi peserta yang hadir. Hasil kegiatan menunjukkan terjadi peningkatan pemahaman peserta terhadap stunting dan upaya pencegahannya. Hal ini dapat dilihat dari antusiasme saat menjawab pertanyaan pemateri. Pelaksanaan kegiatan juga meningkatkan kemampuan pengolahan bahan pangan sekkitar menjadi produk preventif stunting. Aspek pemahaman dan pengolahan produk nutraceutical merupakan upaya pemberdayaan yang berhasil dilakukan serta menjadi tujuan dari pengadaan kegiatan